FOREIGN EXPERIENCE OF PROVIDING ROAD SAFETY BY PATROL POLICE - Kozar, D. (Honor and Law, 2020)
Road safety in modern conditions is one of the most important tasks in the context of the protection and protection of human and citizen’s rights and freedoms. The increase in the number of vehicles, the rapid increase in the number of cases of committing offenses on the road, the low technical characteristics of vehicles are the reasons for the need to increase the theoretical and practical support of processes for the organization of traffic safety. Road safety is a multifaceted issue that includes not only the control of moving vehicles, but also the creation of conditions where pedestrians have the ability to navigate established places without creating an accident on the road. This article analyzes the concept and nature of patrol police activity in Ukraine in the context of implementing road safety measures. The concept of traffic safety is considered, identified and argued that includes the provision of road safety by the patrol police within the framework of the current legislation, namely, the Law of Ukraine “On National Policeˮ, the essence of the corresponding concept is highlighted. The need to use foreign practices in the process of organizing road safety, as well as in training of its perpetrators, was stated. Based on the analysis of foreign experience in the field of road traffic safety, as well as statistics on the activities of the police in general and the patrol police in particular, in the field of road safety, a number of conclusions and recommendations, the practical application of which will contribute to improving the level of road safety. It is stated that the experience of different foreign countries should be analyzed, consolidated and modernized in the light of current Ukrainian realities, and further integrated into the existing system of road safety in Ukraine.